Randomized controlled trial assessing plaque removal of an oscillating‐rotating electric toothbrush with micro‐vibrations. (3rd April 2020) - Adam, Ralf; Erb, Jasmin; Grender, Julie
Abstract : Objective: The objective was to assess plaque removal potential of a newly designed oscillating‐rotating (O‐R) electric rechargeable toothbrush with micro‐vibrations compared to a manual toothbrush. Methods: This was a randomized single‐brushing, two‐treatment, examiner‐blind, replicate‐use, four‐period crossover design study, conducted with three cohorts of nine subjects each, with all subjects using each toothbrush twice. Test toothbrushes included a new O‐R rechargeable electric toothbrush with micro‐vibrations (Oral‐B iO prototype) and a manual American Dental Association (ADA) reference toothbrush. On each of the four study visits, subjects refrained from oral hygiene for 12 hours prior. At each visit, subjects received a pre‐brushing plaque examination, brushed with their assigned toothbrush and a marketed fluoride dentifrice and then received a post‐brushing plaque examination. Plaque was assessed using the expanded Turesky Modified Quigley‐Hein Plaque Index. Treatment comparison analyses were two‐sided and carried out at the 5% significance level. Results: All 27 randomized subjects (mean age = 42.0 years) completed the trial. Both brushes produced significant plaque reductions versus baseline ( P < 0.001). The O‐R electric brush provided statistically significantly greater plaque reductions in all regions compared to the regular manual toothbrush, with a between‐treatment difference of 0.929 for whole mouth plaque, 0.965 for proximal plaque, 1.029 for lingual plaque and 0.815 for facial plaque ( P < 0.001 for all comparisons). Additionally, use of the novel O‐R brush yielded greater brushing evenness/consistency when comparing the facial and lingual mean plaque removal differences relative to manual brushing ( P = 0.001). Both brushes were well‐tolerated. Conclusion: The novel O‐R toothbrush with micro‐vibrations produced significantly greater plaque reductions compared to the manual toothbrush.